How much do firms hedge with derivatives? - Guay, Wayne; Kothari, S.P (Journal of Financial Economics, 2003)
For 234 large non-financial corporations using derivatives, we report the magnitude of their risk exposure hedged by financial derivatives. If interest rates, currency exchange rates, and commodity prices change simultaneously by three standard deviations, the median firm's derivatives portfolio, at most, generates 15 million in cash and 31 million in value. These amounts are modest relative to firm size, and operating and investing cash flows, and other benchmarks. Corporate derivatives use appears to be a small piece of non-financial firms’ overall risk profile. This suggests a need to rethink past empirical research documenting the importance of firms’ derivative use.